Pengaruh Live Streaming, Flash Sale, Online Customer Review Terhadap Keputusan Pembelian Pada Tiktokshop (Studi Kasus Pada Mahasiswa Manajemen FEB UNISMA Angkatan 2020) - Fanely Yane, Sultan Nuur Fanaul Akbar; Wahono, Budi; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
The purpose of this study is to determine how online customer reviews, flash sale, and live streaming affect purchases made on Tiktok Shop. The research's target demographic consists of 2020 FEB UNISMA Management students who utilize Tiktok Shop. Multiple linear analysis approaches are employed in this data analysis procedure. Purposive sampling, which is a sampling strategy based on respondents' criteria—that is, those who have made purchases from the Tiktok Shop—was employed in this study. The study's findings indicate that Tiktok Shop buyers are influenced by live streaming and flash deals. Online customer reviews, however, have no bearing on selections made about what to buy on Tiktok Shop. Keywords : Live Streaming, Flash Sales, Online Customer Review And Purchase Decisions